APLIKASI BACTERIAL COLONY OPTIMIZATION UNTUK OPTIMALISASI PRODUKSI - Yennimar Yennimar; Sunarly Wijaya; Antonius Nyomadi (Jurnal Mantik Penusa)
In implementing the production of goods, companies often have difficulty in managing the production process so as to maximize the use of existing resources. To do this, it is necessary to optimize production. The simplest method that can be used to optimize production is the Simplex method. However, this Simplex method can only be used to optimize production with one optimization equation. To solve a linear programming model with several optimization equations, several other methods can be used, such as Bacterial Colony Optimization (BCO). This Bacterial Colony Optimization (BCO) algorithm implements the artificial behavior of bacteria. The basic behavior of bacteria in the life cycle can be separated into four parts, namely chemotaxis, reproduction, migration and communication. Based on the tests carried out, obtained information that the BCO method can minimize the required production costs, but the production time required is longer.